Trained immunity in monocyte/macrophage: Novel mechanism of phytochemicals in the treatment of atherosclerotic cardiovascular disease - Wang, Jie; Liu, Yong-Mei; Hu, Jun; Chen, Cong (Frontiers in Pharmacology, 2023)
Atherosclerosis (AS) is the pathology of atherosclerotic cardiovascular diseases (ASCVD), characterized by persistent chronic inflammation in the vessel wall, in which monocytes/macrophages play a key role. It has been reported that innate immune system cells can assume a persistent pro-inflammatory state after short stimulation with endogenous atherogenic stimuli. The pathogenesis of AS can be influenced by this persistent hyperactivation of the innate immune system, which is termed trained immunity. Trained immunity has also been implicated as a key pathological mechanism leading to persistent chronic inflammation in AS. Trained immunity is mediated via epigenetic and metabolic reprogramming and occurs both in mature innate immune cells as well as their bone marrow progenitors. Natural products are a promising candidate for novel pharmacological agents that can be used to prevent or treat cardiovascular diseases. A variety of natural products and agents exhibiting anti-atherosclerotic abilities have been reported that potentially interfere the pharmacological targets of trained immunity. This review describes in as much detail as possible the mechanisms involved in trained immunity and how phytochemicals of this process inhibit AS by affecting trained monocytes/macrophages.